A study on the Agent of Multilevel Marketing (MLM) in Sabah - Shaierah Gulabdin; Toh, Pei Sung; Stephen Laison Sondoh Jr. (Asian Scholars Network, 2021)
The MLM sector is expected to gain traction and contribute to the development of the Malaysian economy. The Multilevel Marketing (MLM) business, on the other hand, has difficulties in recruiting and keeping agents. Instead of focusing on the agent’s sales performance, as many scholars have done in the past, the researcher wants to concentrate on the agent’s performance, which is considered the service quality based on contextual performance. In Sabah, MLM agent performance is inconsistent since it is difficult for them to maintain their downline to remain in the MLM company, and there is a lack of upline support or identification. Existing practices and gaps have been identified via a review of previous research and literature. This research looks at the relationship between interpersonal identification and the agent’s performance, specifically in the Sabah Multilevel Marketing (MLM) sector. The Big Five Factors (BFF) of personality characteristics are used in this research. The main five factors are insufficient to characterize the agents fully. The agent’s interpersonal identification will play a significant part in forecasting the agent’s performance in the big five-factor model. Implementing the methods described in this research will contribute to societal change by improving the success rate of multilevel marketers, lowering unemployment, and having a beneficial effect on the economy. This study provides value to the MLM business as well as academics.